Cycloserine- and Fluoroquinolone-Induced Seizure in Multidrug-Resistance Tuberculosis (MDR-TB) Patient: A Case Report - Yanifitri, Dewi Behtri; Arliny, Yunita; Utami, Wilia Aprilisa; Winardi, Wira (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Multidrug-resistant tuberculosis (MDR-TB) is a type of tuberculosis (TB) that is resistant to at least two of the most effective first-line anti-TB drugs, isoniazid (H) and rifampicin (R). Cycloserine (Cs) and levofloxacin (Lfx) are second-line anti-TB drugs used in MDR-TB therapy. Even though they are considered to have high effectiveness, both drugs have the potential to cause side effects. One important side effect is neurotoxicity. Seizures have been reported as a common complication of some drugs. Case: A 39-year-old man was diagnosed with MDR-TB and was treated with individual regimens consisting of Lfx, bedaquiline (Bdq), linezolid (Lzd), clofazimine (Cfz), and Cs. After consuming anti-TB drugs for 27 days, the patient had seizures several times. The patient experienced full-body seizures and loss of consciousness during the seizures. Cs and Lfx were discontinued and replaced by other regimens. Serial electroencephalogram (EEG) showed normal results. After Cs and Lfx were discontinued, the patient never had another seizure. Conclusion: Management of MDR-TB is sometimes complicated because of severe drug side effects. Patients taking Cs and fluoroquinolones (FQs) should be advised to report any sign of seizure or changes in mental status to their healthcare provider.